Identification of Critical Biomarkers and Mechanisms of Fructus Ligustri Lucidi on Vitiligo Using Integrated Bioinformatics Analysis - Liang TS; Tang N; Xian MH; Wen WL; Huang CJ; Cai LH; Li QL; Wu YH (Dove Medical Press, 2023)
Tian-Shan Liang,1,* Nan Tang,1,* Ming-Hua Xian,2 Wei-Lun Wen,1 Chang-Jin Huang,1 Lan-Hua Cai,1 Qi-Lin Li,3 Yan-Hua Wu1 1Department of Traditional Chinese Medicine, Guangzhou Red Cross Hospital, Jinan University, Guangzhou, Guangdong, 510220, People's Republic of China; 2School of Chinese Materia Medica, Guangdong Pharmaceutical University, Guangzhou, Guangdong, 510006, People's Republic of China; 3Department of Dermatology, Guangzhou Red Cross Hospital, Jinan University, Guangzhou, Guangdong, 510220, People's Republic of China*These authors contributed equally to this workCorrespondence: Yan-Hua Wu, Department of Traditional Chinese Medicine, Guangzhou Red Cross Hospital, Jinan University, 396 Tongfu Zhong Road, Guangzhou, Guangdong, 510220, People's Republic of China, Tel +86-020-61883742, Email wuyanhua368@163.comObjective: Vitiligo is an autoimmune disease of the skin that targets pigment-producing melanocytes and results in patches of depigmentation that are visible as white spots. Recent research studies have yielded a strong mechanistic understanding of this disease. Fructus Ligustri Lucidi (FLL) has been used for premature graying of hair since ancient China and is currently used to treat vitiligo. However, the key biomarkers and mechanisms underlying FLL in vitiligo remain unclear. This study aimed to identify the potential biomarkers and mechanisms of FLL in vitiligo using network pharmacology analysis.Methods: The expression profiles of GSE65127 and GSE75819 were downloaded from the Gene Expression Omnibus database to identify differentially expressed genes (DEGs) between the vitiligo and healthy samples. Gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment of DEGs were performed using R analyses. We performed R to further understand the functions of the critical targets. Cytoscape tools have facilitated network topology analysis. Molecular docking was performed using Auto Dock Vina software.Results: The results showed that 13 DEGs were screened in vitiligo. Based on bioinformatics, network pharmacology and Western blot, we found that the critical targets of melanoma antigen recognized by 5,6-dihydroxyindole-2-carboxylic acid oxidase (TYRP1) may be related to the mechanism of action of FLL in the treatment of vitiligo.Conclusion: TYRP1, as a melanocyte molecular biomarker, may be closely related to the underlying mechanism of FLL in the treatment of vitiligo via the inhibition of melanocyte death.Graphical Abstract: Keywords: vitiligo, bioinformatics, molecular docking, biomarkers, Fructus Ligustri Lucidi